Mesoporous Sulfonated Carbon Materials Prepared by Spray Pyrolysis. Issue 18 (25th August 2015) - Duyckaerts, Nicolas; Trotuş, Ioan‐Teodor; Nese, Valentina; Swertz, Ann‐Christin; Auris, Sebastian; Wiggers, Hartmut; Schüth, Ferdi
Abstract A one‐step approach was developed for the production of mesoporous sulfonated carbon materials by means of an aerosol synthesis. Nebulizing a clear aqueous solution of sucrose and sulfuric acid through a heated oven leads to subsequent dehydration, carbonization and sulfonation of the carbohydrate structure, in less than two seconds residence time. Acid site concentrations ranging from 0.1 to 0.6 mmol g−1 can be obtained. Porosity can easily be introduced via salt templating, and can be adjusted by varying the loading and type of salt used. The highest surface area was obtained with Li2SO4, giving a BET surface area of 506 m2 g−1 and a mesopore size distribution between 2 and 8 nm. Fructose dehydration and inulin hydrolysis showed that the porous materials synthesized by salt templating are more active than the bulk ones, especially for inulin hydrolysis, for which the initial activity is enhanced by a factor of seven, making these materials competitive with the most active commercial resins.